Aktuelle thermische Klimaveränderungen am Polarrand der Ökumene Europas - Ausmaß, Ursachen und Auswirkungen - Schunke, Ekkehard (ERDKUNDE, 1979)
The warming of the Arctic and its adjacent regions which had begun at the end of the last century, has turned to a temperature depression since the fifties and sixties of our century. In this paper the dimensions, reasons, and consequences of the present temperature depression in the European Sub-arctic are examined, mainly by examples from Iceland. The degree of this thermal climatic change is analyzed by means of those parameters that are relevant to the land use and the morphodynamics: degree days above 0°C, degree days below 0°C, totals of days with alternate freezing and thawing, icedays, and frost intensity. The present temperature depression affects the terrestrial ecological resources in a double way: directly the vegetable production (grass, potatoes), which is the most important basis of the land use in Iceland, is impaired in the course of a reduced summer warmth, and, indirectly, the vegetation potential is disturbed by an intensification of the cryogenic processes. In addition to the change of the cryogenic morphodynamics, which affects indirectly the available potential of the land use, the present temperature depression involves hydrologie changes, namely a reduction of the hydro-energetic potential.